2006
DOI: 10.1016/j.camwa.2006.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Shape preserving surface reconstruction using locally anisotropic radial basis function interpolants

Abstract: In this paper we deal with the problem of reconstructing surfaces from unorganized sets of points, while capturing the significant geometry details of the modelled surface, such as edges, flat regions, and corners. This is obtained by exploiting the good approximation capabilities of the radial basis functions (RBF), the local nature of the method proposed in [1], and introducing information on shape features and data anisotropies detected from the given surface points.The result is a shape-preserving reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 13 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…In this field, fitting with anisotropic directionally dependent covariances is a popular method for ore grade estimation; see Chiles and Delfiner [4]. From the approximation theory community, Cascioli et al [2,3] have demonstrated numerically the effectiveness of local anisotropic RBF fitting, and also that the condition of the matrix solution process is improved.…”
Section: Introductionmentioning
confidence: 99%
“…In this field, fitting with anisotropic directionally dependent covariances is a popular method for ore grade estimation; see Chiles and Delfiner [4]. From the approximation theory community, Cascioli et al [2,3] have demonstrated numerically the effectiveness of local anisotropic RBF fitting, and also that the condition of the matrix solution process is improved.…”
Section: Introductionmentioning
confidence: 99%
“…However, interpolation of data with anisotropic distribution of data sites in the domain requires special consideration. To this end, anisotropic radial basis functions (ARBFs) have been introduced and used in practice [8,9,2]; they are also known as elliptic basis functions as they have hyper-ellipsoidal level surfaces.…”
mentioning
confidence: 99%
“…As already introduced in Section 1, RBF applications recur in many different areas of science and engineering: neural networks in computer graphics (surface reconstruction), solution of partial differential equations, and mesh morphing in image analysis of deformations . RBF mesh morphing has been used for several applications, from FSI coupling to genetic and evolutionary optimizations and advanced modeling …”
Section: Mathematical Backgroundmentioning
confidence: 99%